The influence of mechanochemical treatment of sintered submicrocrystalline corundum substrates on the structure of bioglass composites - Staniewicz-Brudnik, B.; Szarska, S.; Gamrat, K. (Сверхтвердые материалы, 2008)
The influence of mechanochemical treatment of submicrocrystalline sintered corundum on the structure of bioglass composites containing α-Al2O3 and CaO—SiO2—P2O5 glasses was examined in the context of the possibility to form hydroxyapatite after being immersed in the simulated body fluid solution. Measurements of specific surface area and size and X-ray analysis of submicrocrystalline sintered corundum were conducted. Bioglass composites were obtained by placing submicrocrystalline sintered corundum grains in the CaO—SiO2—P2O5 sol system, gelling and sintering at 800 °C. The specimens were examined under a scanning electron microscope before and after immersion in the simulated body fluid solution for 24 and 120 h. Using the VCS algorithm, calculations of thermodynamic stability of compounds occurring in these bioglass composites were carried out, verifying the X-ray analysis.